Little Eight John - Wahl, Jan.; Clay, Wil (New York : Lodestar Books, 1992)
Little Eight John, as mean as mean there was, persists in disobeying his mother until he finds his mischief backfiring on him.
Keywords: African Americans; Folklore -- United States